Hands on Methods for High Resolution Cryo-Electron Microscopy Structures of Heterogeneous Macromolecular Complexes - Serna, Marina (Frontiers in Molecular Biosciences, 2019)
Electron microscopy of frozen hydrated samples (cryo-EM) is a powerful structural technique that allows the direct study of functional macromolecular complexes in an almost physiological environment. Protein macromolecular complexes are dynamic structures that usually hold together by an intricate network of protein-protein interactions that can be weak and transient. Moreover, a standard feature of many of these complexes is that they behave as nanomachines able to undergo functionally relevant conformational changes in one or several complex components. Among all the other main structural biology techniques, only cryo-EM has the potential of successfully dealing at the same time with both sample heterogeneity and inherent flexibility. The cryo-EM field is currently undergoing a revolution thanks to groundbreaking technical developments that have brought within our reach the possibility of solving the structure of biological complexes at atomic resolution. These technical developments have been mostly focused on new direct electron detector technology and improved sample preparation methods leading to better image quality. This fact has in turn required the development of new and better image processing algorithms to make the most of the higher quality data. The aim of this review is to provide a brief overview of some reported examples of single particle analysis strategies designed to find different conformational and compositional states within target macromolecular complex and specifically to deal with it to reach higher resolution information. Different image processing methodologies designed to improve the structural information of biological complexes harbouring a symmetric or pseudo-symmetric arrangements will also be discussed.